An experimental and numerical study of the influence of FGR on NOx formation - Lazić, Ladislav (Materiali in tehnologije, 2004)
In many countries NOx emissions are limited because of their adverse impact on the environment. Different methods to reduce the amount of NOx released into the environment from combustion devices have been developed. The main technique to prevent NOx formation in accordance with the regulation limit at a reasonable cost is flue-gas recirculation (FGR). This paper presents the results of laboratory tests to determine the emissions of nitrogen oxides from a standard natural-gas-fired burner. There was a marked effect on the NOx emissions by varving the excess air and the quantity of recirculated flue gases in the combustion air. A significant reduction in the NOx, by approximately 80 %, was achieved by external flue-gas recirculation. The results obtained from the measurements were compared with those obtained from a calculation of the equilibrium compositions and the adiabatic flame temperature of the combustion products related to the quantity of supplied combustion air and recirculated flue gases.
Keywords: dušikovi oksidi; redukcija; zgorevanje; gorilniki